The Quinoa We Grow - Hernández Cuadra, Daniela (Revue YOUR Review (York Online Undergraduate Research), 2022)
This paper illustrates how quinoa (Chenopodium quinoa Willd.) is an important crop because of its potential to help fight poverty and significantly impact the global food shortage crisis. This work also provides a detailed profile of quinoa as an angiosperm that highlights the notable peculiarities which make the crop highly stress-resistant and adaptable to a wide range of conditions. Two approaches were taken to describe the plant: biological, to highlight its advantages, and sociocultural, to mark its significance. We conclude that the popularity of Chenopodium quinoa Willd. will increase in the upcoming years. This is something to be aware of because, although international organizations are focusing on bringing it to the impoverished, increased popularity and improved reputation typically persuade sellers to increase the price of a product. Thus, a crop selected to fight hunger may become too expensive for those who need it the most.